Assessing skills and measuring performance of students on skills that are aligned with the needs of the 21st Century: A practical example - Tognolini, James (Proceedings of the UR International Conference on Educational Sciences, 2018)
Malaysia is a multi-racial country comprises of diverse lifestyles, cultures as well as religions. This situation requires a different approach in developing the strong values of patriotism in order to preserve the harmony and strengthen the nations identity of Malaysia. The construction of this patriotism framework relies on Malay culture and Islam as the official religion of the country as well as not disregards other ethnic cultures and religions. The goal of patriotism in the context of Malaysia leads to the enrichment of pride values as Malaysian, loyalty to the King and country, have a sense of belonging, has a level of discipline and obedience towards the laws of the country and becoming a competitive and productive society. In order to make this aspiration a reality, various attempts have been made in myriad number of schools, higher education institutes and education as well as community which is driven by the government, private organizations as well as NGOs. Apart from that, a detailed discussion on issues related to the challenges in establishing racial harmony which is a major factor in the formation of Malaysian patriotism framework as well as the suggestions to enforce patriotism among Malaysian nation are also incorporated.